Association of maternal serum zinc and cordblood zinc with neonatal birth weight - Mahmood, Sharmeen; Deeba, Farzana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Zinc is essential for optimal fetal growth because of the role of zinc in cellular division, growth and differentiation. Low maternal serum zinc and cord blood zinc has been reported to be associated with low birth weight and, a risk factor for neonatal morbidity and mortality. The aim of this study was to evaluate the association of maternal serum zinc, cord blood zinc with neonatal birth weight. Methods: This case-control study was conducted in department of obstetrics and gynecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from November 2020 to October 2022. A total of 60 women in their postnatal period were included in this study. Results: In the present study, none of the socio-demographic characteristics in both case and control groups were statistically significant (p>0.05). Mean BMI was 23.88±1.36 kg/m2 in cases and 24.39±1.39 kg/m2 in controls, with 16.7% of cases overweight (p>0.05). Cases had lower maternal serum zinc (58.33±27.63 µg/dl) than controls (82.96±16.94 µg/dl), significantly affecting neonatal birth weight (p=0.001, r=+0.406). Low zinc levels (<68 µg/dl) increased the risk of birth weight <2.500 kg by nearly six times (OR 5.67, 95% CI 1.84-17.49; p=0.002). Conclusions: Low birth weight neonates and their mothers have significant zinc deficiency as compared to term neonates and their mothers and this deficiency is correlated with zinc deficiency in mothers of these low-birth-weight neonates.